Recent advances on cellular therapies and immune modulators for graft-versus-host disease. (October 2014) - Filippini, Perla; Rutella, Sergio
Abstract : The efficacy of allogeneic hematopoietic stem cell transplantation is counterbalanced by the occurrence of life-threatening immune-mediated complications, such as graft-versus-host disease (GVHD), a multistep disease which is reportedly fatal to approximately 15% of transplant recipients. It is now established that T-cell–dendritic cell interactions, T-cell activation, release of proinflammatory cytokines and T-cell trafficking partake in GVHD pathogenesis. This article will focus on the most recent strategies aimed at preventing/treating GVHD by manipulating components of the innate and adaptive immune response from both the donor and the host.